Shareholding characteristics and their relationship with productivity in ecuadorian companies: a quantitative perspective - Freire, Cesar; Hurtado, Gabriela; Calle, Fernando (Revista Venezolana de Gerencia, 2026)
Shareholder characteristics and productivity are critical factors influencing a company’s ability to generate sustainable value, enhance its performance, and secure foreign investment. This study investigates the relationship between these shareholder characteristics and productivity within Ecuadorian companies. Using a quantitative approach, a fixed-effects regression model, adjusted for heteroscedasticity, to a panel of data from 459 companies spanning 2021 to 2022 was applied. Productivity was evaluated using an index developed via exploratory factor analysis. The results demonstrate that certain shareholder characteristics significantly affect productivity. Specifically, shareholder financial health and share ownership concentration show a positive influence, suggesting that engaged shareholders are committed to good corporate governance. Conversely, return on assets exhibits a negative effect. This finding suggests that an excessive focus on short-term profitability may undermine sustainable growth and operational efficiency. In conclusion, improving companies’ productive efficiency requires strengthening the financial stability of shareholders and encouraging greater shareholder engagement. These findings offer guidance for corporate management in Ecuador and pave the way for future research on the interaction between shareholder structure and productivity in different economic contexts.